Combining strength training and botulinum neurotoxin intervention in children with cerebral palsy: the impact on muscle morphology and strength. (April 2013) - Williams, Sîan A.; Elliott, Catherine; Valentine, Jane; Gubbay, Anna; Shipman, Peter; Reid, Siobhan
<x xml:space="preserve">Abstract</x> Purpose: Investigate the combination effects of strength training and Botulinum Toxin Type-A (BoNT-A) on muscle strength and morphology in children with Cerebral Palsy (CP). Methods: Fifteen children receiving BoNT-A, classified as Spastic Diplegic CP, GMFCS I-II, and aged 5–12 years were recruited for this study. Randomly allocated to 10 weeks of strength training either before or after BoNT-A, children were assessed over 6 months. Eight of the 15 children also completed a control period. The Modified Ashworth Scale measured spasticity. The Goal Attainment Scale (GAS) assessed achievement of functional goals. Magnetic Resonance Imaging assessed muscle volume (MV). Instrumented dynamometry assessed strength. Results: Spasticity was significantly reduced following BoNT-A injection (p = 0.033). Children made significant isokinetic strength gains (mean p = 0.022, ES = 0.57) in the intervention period compared to the control period (mean p = 0.15, ES = 0.56). Irrespective of timing, significant strength improvements were seen immediately (10 weeks) and over 6 months for all children. This was also the case for improvements in the GAS (immediately: mean p = 0.007, ES = 4.17, 6 months: mean p = 0.029, ES = 0.99), and improvements in MV in all assessed muscles. Conclusion: The simultaneous use of BoNT-A and strength training was successful in spasticity reduction, improving strength and achieving functional goals, over and above treatment with BoNT-A alone. Muscles targeted for BoNT-A injection should be included in strength training.